Insight into the performance and mechanism of peroxymonosulfate activation by B, N co-doped hierarchical porous carbon for phenol degradation. Issue 5 (October 2022) - Li, Xiaojuan; Ye, Ziyu; Xie, Shuhan; Li, Hongyan; Lv, Yuancai; Wang, Yongjing; Wang, Yonghao; Lin, Chunxiang
Abstract: A series of boron and nitrogen co-doped hierarchical porous carbon materials (BNC) were prepared via a facile one-step calcination process, and the catalytic performance of BNC on PMS activation for phenol removal was investigated. BNC-1 exhibited the optimal catalytic performance with a phenol degradation efficiency of 99.6% within 30 min. B, N co-doping strategy improved the specific surface areas (SSA) and total pore volumes (TPV) of carbon catalysts, providing them with abundant active sites, among which graphitic N and BC3 were identified as critical catalytic sites for PMS activation. Quenching tests, electron paramagnetic resonance (EPR) and electrochemical experiments demonstrated that singlet oxygen ( 1 O2 ) was the dominant active species while surface-bound sulfate radical (SO4 ·- ) played an inferior role in the BNC-1/PMS/Phenol system, and the role of hydroxyl radical (·OH), superoxide radical (O2 ·- ) and surface electron transport cannot be ignored either. The coexistence of radical and non-radical oxidation processes made BNC-1/PMS system have excellent acid-base tolerance (pH=3–11), anti-interference ability and pollutant mineralization performance (68.3% of TOC removal within 30 min). This study presented a high-efficiency and environment-friendly B, N co-doped metal-free catalyst for pollutants degradation via PMS activation and provided an in-depth research for the mechanism of PMS activation by BNC. Graphical Abstract: ga1 Highlights: B, N co-doped hierarchical porous carbon was synthesized by one-step pyrolysis. Phenol can be completely degraded by BNC-1/PMS with TOC removal of 68.3%. BNC-1/PMS present excellent acid-alkali resistance (pH=3–11) and anti-interference ability. The non-radical pathway ( 1 O2 ) dominated in BNC-1/PMS system for phenol removal. Graphitic N and BC3 contribute to 1 O2, radical generation and electron transfer.